OFDM frequency offset estimation based on BLUE principle - Minn, H.; Tarasak, P.; Bhargava, V.K. (Proceedings IEEE 56th Vehicular Technology Conference, 2002)
High performance frequency estimation is an important issue in orthogonal frequency division multiplexing (OFDM) systems since OFDM systems are very sensitive to carrier frequency offsets. Recently, M. Morelli and U. Mengali (M&M) presented a near optimal frequency estimator based on the best linear unbiased estimation (BLUE) principle (see IEEE Commun. Letters, vol.3, no.3, p.75-7, 1999). We present three frequency estimation methods based on the BLUE principle. The third method has the same frequency estimation mean square error (MSE) performance as the M&M method. The first two methods give better MSE performance than the M&M method, especially at low SNR values. The first two methods' MSE performances are essentially the same and quite close to the Cramer-Rao lower bound for all SNR values; hence, these proposed methods are very attractive for OFDM applications.